Jet-loop reactor with cross-flow ultrafiltration membrane system for treatment of olive mill wastewater - Ribeiro, Belina (2018)
ABSTRACT: Olive oil extraction is one of the ancient agricultural industries all over the Mediterranean area and even today it is of fundamental economic importance for many industries found over the whole Mediterranean. However, this industry generates large amounts of olive mill wastewater (OMW) and due to its physicochemical characteristics it causes severe environmental concerns and management problems in the Mediterranean area, which is facing water scarcity. Technologies to reuse this wastewater will have a high impact at the economic and environmental level. The work presented aims to improve the use of jet-loop reactors technology for the aerobic biotreatment of OMW. A jet-loop reactor (100 L) coupled with an ultrafiltration (UF) membrane (MBR) system (JACTO.MBR_100 L) were tested for the influence of hydraulic parameters on OMW degradation and scale-up to 1,000 L. Chemical oxygen demand and total phenols (TP) decreased notably (up to 85% and 80% removal efficiency, respectively) after the biological treatment. The treated OMW (UF permeate) was evaluated as a source for irrigation and its impact on the soil and plant growth and their quality parameters.